The Influence of Live Streaming Shopping, Content Quality, and Customer Engagement on Purchase Intention with Consumer Trust as an Intervening Variable on Tiktok Shop Consumers - Ifani Wahyururiasanti; Lidhiatul Izzah; I Made Suparta; Ida Bagus Cempena (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the rapid evolution of TikTok Shop in Indonesia, which has transformed into one of the largest social commerce markets in Southeast Asia through the integration of entertainment and e-commerce. The research aims to analyze the impact of live streaming shopping, content quality, and customer engagement on consumer trust and purchase intention. Using a quantitative methodology, data were collected from 125 TikTok Shop consumers in Surabaya and analyzed using Partial Least Square (PLS). The results demonstrate that all seven proposed hypotheses are significantly supported, with live streaming shopping emerging as the most dominant factor in building trust and driving purchase intention due to its transparent, real-time interactive nature. Theoretically, these findings validate the Stimulus-Organism-Response (SOR) and Social Exchange Theory (SET) frameworks in the context of digital social commerce. The study concludes that a synergy between seller credibility, aesthetic information, and active audience participation is crucial for commercial success, suggesting that TikTok Shop prioritize the optimization of live streaming features and authentic content to mitigate perceived transactional risks.